A 13 Years Statistical Evaluation on Maxillofacial Malignant Tumors in Hamedan - M. H Ansari (Tehran University of Medical Sciences, 2003)
Cancer is considered as one of human's complications, particularly in oral and maxillofacial region which leads to undesirable effects and sometimes endangers individual's life. The aim of this study was to investigate the frequency of maxillofacial malignant tumors, during 13 years, (1985- 1998), in Hamedan. Three hundred and eighty - six records of biopsies were selected from the private files of physicians, 7 private and governmental pathological centers and other educational and research organizations in Hamedan. After observing the samples by oral pathologist, they were presented as thestatistical population for this retrospective study. The highest rate of biopsies was observed in the sixth (42.7%), seventh (39.6%) and third (10.6%) decades. The average age was 43.5 years, for women and1.52 45.5 for men. The ratio of men to women was . The oldest patient was a 91- year - old man with malignant melanoma, while the youngest was a 3-year-old girl with Burkit lymphoma. The commonest site of involvement was nasal region (17.3%) and the anterior neck triangle showed the least common tumoral site (2.3%). The commonest tumor, observed in this study, was BBC (41.4%) and the least common was malignant fibrous histocytoma (0.2%). Baso cellular and epidermoid carcinomas have been the commonest cancers in this investigation, while lymphoma and salivary galnd cancers have been placed as the second ones. The results of this study showed that the lower lip and tongue are considered as the commonest sites for cancer.